ARCS STRATEGY (ATTENTION, RELEVANCE, CONFIDENCE, SATISFACTION) IN MATHEMATICS LEARNING - Nancy Katili; Lazna Suci Wali (Jurnal Bahasa, Sastra, dan Budaya, 2021)
This library research examined previous scientific papers on ARCS (Attention, Relevance, Confidence, Satisfaction) strategy. This research aimed to create a mathematics learning scenario by implementing the ARCS strategy. The qualitative data were from secondary data, i.e., several literature reviews from previous studies. Moreover, the data were collected through documentation, or in this case, collecting data based on theories, books, and journals that discussed ARCS strategy. The data were analyzed by describing the data from previous studies, and were then processed to produce a mathematics learning scenario based on the ARCS strategy. This can be applied by math teachers during the lesson